Customer‐centric regulation: The case of Victorian urban water sector. Issue 2 (18th October 2020) - Ananda, Jayanath; Pawsey, Nicholas; Nayeem, Tahmid
Abstract: The growing interest in customer engagement (CE) has triggered a new wave of reforms, particularly in utility regulation. Within the water sector, there has been a shift from a focus on cost‐reflective pricing toward customer‐centric pricing processes designed to identify customer preferences and expectations. The Victorian water sector in Australia offers a unique opportunity to explore the outcomes of these CE trends given the recent first‐time application of a novel Performance, Risk, Engagement, Management, and Outcomes (PREMO) framework. Based on in‐depth interviews with senior industry representatives from a diverse sample of Victorian water utilities, this paper critically analyses the scope, design, and incentive mechanisms that underpin the new regulatory process. Findings indicate that CE has potentially beneficial aspects to both the regulator and the regulated utility, including more transparency in capital projects and a better understanding of customer preferences in service delivery.